Development of Chemical Literacy Oriented Speed Cruiser Interactive Multimedia on Reaction Rate Material - Nurfazhira, Ratu Tiara; Sari, Sari; Irwansyah, Ferli Septi (LAVOISIER: Chemistry Education Journal, 2025)
The purpose of this study is to analyze the results of the validation test and describe the appearance of the chemical literacy-oriented Speed Cruiser multimedia on the developed reaction rate material. The novelty aspect of this research lies in the delivery of chemical content in the multimedia developed, not only discussing chemical concepts thoroughly, but also integrating the four aspects of chemical literacy, namely content, context, scientific process, and scientific attitude, in one application that can be accessed through various devices. This research uses the Design-Based Research (DBR) method with the stages of analysis, design, and development. The types of data used are quantitative and qualitative data. Quantitative data was obtained through validation tests and feasibility tests. The validation test was carried out by material experts and media experts, while the feasibility test was carried out by high school students in class XI IPA who participated in IT extracurricular activities. The qualitative data is obtained from suggestions for improvement from validators and respondents. The validation test results for this study obtained an average rcount of 0.89 for all aspects, and the percentage of feasibility test results obtained a value of 86%. This shows that the Speed Cruiser multimedia is declared valid and feasible to use in learning.